Network disruption detected in NC (New Caledonia) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in New Caledonia. Data sourced from IODA.
Network Disruption Incident ID: NC-2026-0001. Severity: critical. Confidence: 67%